Main Directions of Effective Influenza Prevention in Modern Conditions - E. I. Burtseva; E. A. Mukasheva; A. G. Rosatkevich (Эпидемиология и вакцинопрофилактика)
This paper presents the risk analysis of influenza virus infection in different age groups based on the prevalence and mortality rates. The epidemiological characteristics of the influenza virus circulation during postpandemic period are given. Main aspects of specific and non-specific influenza prevention are discussed. The efficacy of the interferon-based medication Grippferon in the prevention of influenza and acute respiratory viral infections (ARVI) is justified.